Meningkatkan Loyalitas Pelanggan melalui Kualitas Pelayanan, Harga, dan Promosi - Purba, Ijah Sani; Amelia, Ocdy (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
In the competitive retail industry, understanding the factors that influence customer loyalty is crucial for business success. This study aims to explore the impact of Service Quality, Price, and Promotion on customer loyalty. As retail businesses face increasing complexity and the need to meet evolving consumer demands, identifying the right strategies to maintain and enhance customer loyalty becomes essential. This research adopts a quantitative descriptive approach, utilizing a sample of 54 respondents to examine these relationships. The findings reveal that Service Quality significantly and positively influences customer loyalty, with a t-value of 2.163, which exceeds the t-table value of 2.00856, and a significance level of 0.035 (<0.05). Similarly, Price has a significant and positive partial effect on customer loyalty, as indicated by a t-value of 2.528 and a significance level of 0.015 (<0.05). Promotion also demonstrates a significant and positive partial effect, with a t-value of 2.872 and a significance level of 0.006 (<0.05). When considered together, Service Quality, Price, and Promotion have a significant effect on customer loyalty, as reflected by an F-value of 21.332, which is greater than the F-table value of 2.79, with a significance level of 0.000 (<0.05). These results underscore the importance of developing and implementing strategies that focus on service excellence, competitive pricing, and effective promotions to foster customer loyalty in the retail sector.